Software metrics for attribute understandability - Луцький, М.Г.; Дишлевий, О.П. (Proceedings of National Aviation University (archive), 2010)
The article is dedicated to selection of software metrics for attribute understandability. The attribute understandability has been analyzed and selection of metrics has been made by «goal-question-metrics» method. Data collection has been made with using subject-oriented method of making dependences between software metrics. As a result of analysis software metrics has been confirmed for attribute understandability. Validity of each metric was calculated for this attribute.